Islamic Bank Financing, Green Sukuk, and the Jakarta Islamic Index: An ARDL Analysis of Indonesia’s Real Sector - Hidayat, Rahmad; Jazilinni’am, Naili; Rusgianto, Sulistya; Ratnasari, Ririn Tri; Ryandono, Muhammad Nafik Hadi (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2025)
This study examines the effects of Islamic Bank Financing (IBF), Green Sukuk (GS), the Jakarta Islamic Index (JII), inflation (CPI), exchange rate fluctuations (EXR), and money supply (M2) on Indonesia’s real sector using the Autoregressive Distributed Lag (ARDL) approach. The findings reveal that IBF stimulates the real sector in the short run, but structural challenges and limited market penetration constrain its long-term influence. Conversely, GS exerts a significant positive impact over the long term, underscoring the importance of sustainable investments in enhancing productive capacity and generating employment. Although JII shows no significant short-term effect, it contributes meaningfully in the long run. CPI consistently exerts a negative influence on the real sector in both horizons, while exchange rate appreciation and M2 growth support economic activity. These results highlight the need for coordinated policy measures to foster inclusive, stable, and sustainable development in Indonesia’s real economy.